ChemInform Abstract: Synthesis of Novel Pyrano[3, 2‐f]quinoline, Phenanthroline Derivatives and Studies of Their Interactions with Proteins: An Application in Mammalian Cell Imaging. Issue 28 (15th July 2014) - Majumdar, K. C.; Ponra, Sudipta; Ghosh, Tapas; Sadhukhan, Ratan; Ghosh, Utpal
Abstract Derivatives (II) are able to stain cultured Hela cell after fixing and give fluorescence at the sky blue region.